Consumer Sensory Perception and Food Quality: Sensory Branding Trends - Vivy Kristinae; Leiden, Bryan Ivano Gavrielo; Leiden, Jeany Felicia Audrea (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
The COVID-19 pandemic in Indonesia has had a significant negative impact on the agricultural economy of the country's most populous province, Kalimantan Tengah. The implications of research have an impact on regional economic stability due to consumer-product quality and revenue sharing during pandemics. Method for doing a deskriptif analysis combined with a deskript analysis of 200 consumers in Tengah Kalimantan. Based on the results of an analysis using regressive SPSS 24.0, it was concluded that consumer perception management is crucial for improving product quality and increasing sales by at least 73%. Accordingly, the results of this study provide support and a positive impact on business operations in the field of consumer psychology in order to better understand business systems through the use of consumer psychology in Central Kalimantan-Indonesia.